2007
DOI: 10.1016/j.bbr.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuits underlying crying and cry responding in mammals

Abstract: Crying is a universal vocalization in human infants, as well as in the infants of other mammals. Little is known about the neural structures underlying cry production, or the circuitry that mediates a caregiver's response to cry sounds. In this review, the specific structures known or suspected to be involved in this circuit are identified, along with neurochemical systems and hormones for which evidence suggests a role in responding to infants and infant cries. In addition, evidence that crying elicits parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
141
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 118 publications
2
141
0
4
Order By: Relevance
“…In addition, human vocalizations could be traced down to their evolutionary roots by comparing them with the vocalizations of our nearest primate relatives (Brudzynski, 2014;Ross, Owren, & Zimmermann, 2009;Sauter, Eisner, Ekman, & Scott, 2010). Evidence of phylogenetic parallels strongly supports the claim that certain nonlinguistic vocalizations correspond to innate call types, and such evidence is indeed becoming available for both laughter (Ross et al, 2009) and crying (Newman, 2007). Naturalistic human vocalizations recorded in real-life contexts are particularly valuable for phylogenetic reconstruction, because they are more likely to be produced unintentionally, bypassing language-like and culture-specific modifications.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, human vocalizations could be traced down to their evolutionary roots by comparing them with the vocalizations of our nearest primate relatives (Brudzynski, 2014;Ross, Owren, & Zimmermann, 2009;Sauter, Eisner, Ekman, & Scott, 2010). Evidence of phylogenetic parallels strongly supports the claim that certain nonlinguistic vocalizations correspond to innate call types, and such evidence is indeed becoming available for both laughter (Ross et al, 2009) and crying (Newman, 2007). Naturalistic human vocalizations recorded in real-life contexts are particularly valuable for phylogenetic reconstruction, because they are more likely to be produced unintentionally, bypassing language-like and culture-specific modifications.…”
Section: Discussionmentioning
confidence: 75%
“…This learning may even happen in utero, so that newborn babies already cry with the typical prosody of their mother's native language (Mampe, Friederici, Christophe, & Wermke, 2009). However, such variation by no means prevents the basic acoustic type from being recognized as crying (Newman, 2007), just as the pant-hoots of wild chimpanzees are readily recognizable as pant-hoots, although subtle group-specific acoustic differences have been described (Crockford, Herbinger, Vigilant, & Boesch, 2004).…”
mentioning
confidence: 99%
“…Many examples have showed that infant mammals evolved signals to maintain maternal responsiveness (Gonzalez-Mariscal and Rosenblatt, 1996;Charrier et al, 2002), to alert parents about pup separation (Kober et al, 2007) or imminent attacks by predators or conspecifics (Blumstein and Daniel, 2004). Based on the evidence that common neural structures and neurochemical systems in different mammals underlie the production and perception of these vocalisations, Newman (2007) proposes their inclusion in a functional category called 'crying', common to all mammalian infants and the adults of some species. The proposed function of these calls is the re-establishment of contact between mother/caretaker and infant.…”
Section: Introductionmentioning
confidence: 99%
“…131 First, the collection of pain cries allowed for a standard procedure 132 that could be implemented across all data collection sites (see 133 below). Secondly, there is research to indicate that the neural 134 circuitry differs between pain cries and spontaneous cries [15,16]. 135 An infant's response to pain is one of extreme stress-arousal and is 136 a form of involuntary expression; whereas spontaneous cries 137 spontaneous cries reflect a form of voluntary expression [17].…”
mentioning
confidence: 99%